A role and value of victimization factor are in a criminal trial (Journal of actual problems of jurisprudence, 2019)
This article discusses the key issues of victimization of knowledge in criminal proceedings. We study the patterns of emergence,transformation and disappearance interconnections and interdependencies between victimization factor, the mechanism of the crimeand the participation of stakeholders in the criminal procedure law relations. The article also examines the legal means and methods ofprotecting the legitimate interests of the individual and the state through the use of victimization knowledge.